The impact of clinical factors, riluzole and therapeutic interventions on ALS survival: A population based study in Modena, Italy. Issue 5 (September 2013) - Georgoulopoulou, Eleni; Fini, Nicola; Vinceti, Marco; Monelli, Marco; Vacondio, Paolo; Bianconi, Giorgia; Sola, Patrizia; Nichelli, Paolo; Mandrioli, Jessica
Abstract: The prognostic role of riluzole, enteral nutrition (EN), non-invasive ventilation (NIV) and interdisciplinary care in ALS is still debated. A population based study has been performed focusing on ALS survival, with particular attention to prognostic factors and therapeutic intervention. All patients diagnosed with ALS between 2000 and 2009 and residing in Modena, Italy, have been registered. A centre for motor neuron disease (MND) has been active in our province since 2000, in addition to a prospective registry collecting all incident cases. One hundred and ninety-three incident cases have been collected during the 10 years of the study. Results demonstrated that median survival was 41 months (the overall three-year and five-year survival rates being 54.36% and 28.81%, respectively). Based on univariate analysis, factors related to survival were: age at diagnosis, gender, site of onset, phenotype, riluzole treatment and tracheostomy. In the Cox multivariable model, the factors independently related to a longer survival were age ( p < 0.01), site of onset ( p = 0.02) and riluzole treatment ( p < 0.01), with a median gain in survival of 29 months (patients aged < 55 years compared with patients ≥ 55 years), 20 months (spinal versus bulbar onset), and 12 months (riluzole, yes vs. no), respectively. In conclusion, the study has confirmed the prognostic role of clinical features, but has surprisingly demonstrated that riluzole prolonged life significantly longer than NIV and EN. This observational study described the effects of ALS management in a setting that may approximate routine clinical practice more closely than randomized controlled trial (RCT); effects of uncontrolled potential confounders, however, cannot be excluded.